Efficient In Vitro Somatic Embryogenesis and Plant Regeneration from Mature and Immature Embryos of Wheat ( Triticum aestivum L.) - Ahmadpour,Roghayeh (2016)
ABSTRACT An efficient regeneration system is a pre-requisite for the application of genetic transformation and functional genomics study of important plants. In this study, the effect of different factors (plant growth regulators, casein hydrolysate, aspartic acid and ascorbic acid) on in vitro embryogenesis and regeneration of Arta, Bahar and Zagros cultivars from mature and immature explants were investigated. Immature and mature embryos were dissected from disinfected seeds 20-25 days after pollination and imbedded mature seeds, respectively, and cultured on MS (Murashige and Skoog) medium supplemented with different compounds. The results showed that immature embryos expose high capacity of embryogenesis and regeneration in comparison with mature embryos. There were significant differences between cultivars in terms of the percentage of callus induction and regeneration. Plant growth regulators had significant effect on percentage of callus induction in mature explants and percentage of regeneration from both explants. In immature explants, the highest percentage of regeneration (65%) was achieved with the Arta cultivar calli derived from MS medium supplemented with 1mg/L 2,4-D, 2 mg/L Picloram and 200 mg/L casein hydrolysate, and subcultured on MS medium. Also, the highest percentage of regeneration (52.38%) from mature embryo explants was achieved in the Arta cultivar with callus induction on MS medium supplemented with 1 mg/L 2,4-D, 2 mg/L Picloram and 200 mg/L casein hydrolysate and regeneration on MS medium containing 0.05 mg/L NAA.